Analysis of Efficiency and Heat Transfer Coefficient in the Performance Evaluation of Shell and Tube Heat Exchanger - Chalimah , S; Maulana , I; Setyobudi, R; Sandrina, A; Anggoro , R B; Buana , E S; Kartiko, M A; Alhalim, MA (BIOMEJ, 2024)
Heat transfer is the process of energy transfer from a region of higher temperature to a region of lower temperature, occurring through conduction, convection, and radiation mechanisms. Understanding heat transfer is crucial in various industrial and thermodynamic applications. One commonly used device in this process is the heat exchanger, which allows heat transfer between two fluids with different temperatures without direct mixing. This research aims to evaluate the heat transfer phenomena in heat exchangers and their performance under various operational conditions. The study measured the average temperature difference, kinematic viscosity, Reynolds number, fluid velocity, heat exchanger efficiency, the average heat released and received, and the heat transfer coefficient. The results showed a high heat exchanger efficiency, with an average value of 99.53%. The heat transfer coefficient also showed significant values, varying based on fluid flow type and operational conditions. This study emphasizes the importance of selecting the appropriate type and design of heat exchanger to improve thermal system efficiency and reduce energy consumption.